Penerapan Prinsip-Prinsip Good Governance Pada Kantor Badan Pemeriksa Keuangan (BPK) Perwakilan Provinsi Gorontalo - Rahayuningsih, Tri Widyawati; Igirisa, Irawaty; Sulila, Ismet (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The implementation of the current system of government is all towards the system of Good Governance. The aim of this study is to analyse the extent to which the principles of Good Governance (accountability, transparency, openness and rule of law) are applied to the BPK Office of the Provincial Representative of Gorontalo. The research methods used in this research are qualitative methods, and the research produced is descriptive data which means that the data is obtained from writing, words or speech. The results of the research show that the application of the principles of Good Governance to the BPK Office of the Provincial Representative of Gorontalo has been well implemented. The implementation of accountability in the BPK office has been reflected in the character of the staff in the office which is responsible, professional, careful, thorough and with a high degree of integrity. On the application of the principle of transparency seen from the honest, objective, and impeccable service, just need to be enhanced on the update of information on the website. Regarding the implementation of openness, the BPK Office provides a special place for the public who will give criticism and advice. The last one relates to the rule of law, all the officers in duty are as orderly, disciplined and not deviating from the existing rules.